Effects of fluorinated pyrimidines on the growth of excised pea embryos - Paranjothy, K.; Raghavan, V. (Oxford University Press, 1970)
The effects of some fluorinated pyrimidines on the growth of excised pea embryos {Pisum sativum var. Alaska) in sterile culture were studied. Even the lowest concentrations of the compounds tested inhibited growth in length of the embryos. In order of decreasing activity, the compounds tested were : 5-fluorodeoxyuridine, 5-fluorodeoxycytidine, 5-fluorouridine, 5-fluoroorotic acid and 5-fluorouracil. Inhibition of growth in length of the root primordia was found to be mainly due to inhibition of cell division with no effect on cell elongation. Reversal of fluoropyrimidine induced inhibition of growth by pyrimidine bases and their related metabolites indicated that the analogues primarily inhibited DNA synthesis. © 1970 Oxford University Press.